Materials and processing route for aircraft brake system - Maleque, Md. Abdul; Abdullahi, U. (Universiti Malaya, 2013)
Research works are being done to substitute heavy material with a suitable lighter weight and cheaper material which has better properties for this particular application. Processing route plays a significant role in developing the material for any application with effective cost and environmental factors and careful selection of processing route is especially very important for brake disc material. In this paper, a comprehensive review has been done on material and processing route in view of selecting alternative lightweight and cheaper materials for aircraft brake disc application. The advantages and disadvantages between aluminium metal matrix composite and other materials as well as the advantages of powder metallurgy route with other processes are presented for better understanding of the materials and process selection. Finally, emphasis has given on lightweight and cheaper carbon nanotube aluminium matrix (CNT-Al) nano-composite material with specific processing route as a case study. This is mainly based on material selection using material selection process which showed CNT-Al as an excellent candidate material for brake disc application.